Refugee-entrepreneurship: a social capital perspective - Bizri, Rima M. (Entrepreneurship and regional development, 2017)
This paper seeks to identify the characteristics of refugee-entrepreneurial startups, which distinguish them from other immigrant entrepreneurial ventures. The author employed a single case analysis as a means of qualitative research into the phenomenon under study, from the perspective of social capital theory. A typical case of a refugee entrepreneur was selected based on his propensity to tell his story in a way that transparently reveals the various peculiarities of his entrepreneurial behavior. The case study involved the use of interviews with key individuals, the review of printed materials, and member checking. The findings revealed five distinctive attributes that characterized that startup and which corresponded to the three dimensions of social capital. Those attributes were: a 'one-way-ahead' attitude, a pseudo family business perception, collective bootstrapping, a distinct network structure, and opportunity-seizing proliferation, thereby depicting how social capital is used by refugee-entrepreneurs to maximize the pool of opportunities in their host nations.